2016
DOI: 10.3892/mmr.2016.5199
|View full text |Cite
|
Sign up to set email alerts
|

Chronic effects of soft drink consumption on the health state of Wistar rats: A biochemical, genetic and histopathological study

Abstract: The present study was performed to examine the effects of chronic soft drink consumption (SDC) on oxidative stress, biochemical alterations, gene biomarkers and histopathology of bone, liver and kidney. Free drinking water of adult male Wistar rats was substituted with three different soft drinks: Coca-Cola, Pepsi and 7-Up, for three consecutive months. The serum and organs were collected for examining the biochemical parameters associated with bone, liver and kidney functions. Semi-quantitative reverse transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 43 publications
(48 reference statements)
1
25
0
Order By: Relevance
“…Alkhedaide et al, 2016 [24] mentioned that caffeine in carbonated beverages is added to make individuals addicted and is readily absorbed rapidly compared with any other drink. This might explain the increase in average Diet Coke intake in rats of group II and group IV as compared to the average water intake of control rats in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Alkhedaide et al, 2016 [24] mentioned that caffeine in carbonated beverages is added to make individuals addicted and is readily absorbed rapidly compared with any other drink. This might explain the increase in average Diet Coke intake in rats of group II and group IV as compared to the average water intake of control rats in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The inability of antioxidant defense mechanisms to scavenge excessive levels of reactive oxygen species (ROS) and/or reduction in the basal antioxidant defense mechanisms are the primary causes for oxidative stress in tissues (17). Therefore, degenerative diseases, including hepatopathies are caused by this oxidative stress (17,18). Lipid peroxidation is demonstrated to induce disturbance of membrane function and integrity (19).…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that carbonated beverages induced oxidative stress and change of the expression of certain genes associated with brain activity. Alkhedaide in his study also associated the consumption of soft drinks in rodents with the increase of oxidative stress biomarkers, and besides that with a disruption in the expression of certain genes associated with liver and kidney functions [8] [9].…”
Section: Introductionmentioning
confidence: 96%